THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION - Isniati; Muhammad Aqsa; Rismawati; Imam Pribadi; Duriani, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to analyze the influence of service quality on customer loyalty through customer satisfaction at the Memed Welding and Dico Workshop in Palopo City. This research is expected to help the Memet Workshop in solving the problems faced in accordance with the topics taken by the researcher by analyzing data on the influence of service quality on customer loyalty through customer satisfaction. This study uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to customers of Memed Welding and Dico Workshops. The population is a customer of the Memed Workshop with an incidental sampling technique. The number of samples was determined using the MoE formula so that the number of samples was 96 samples. The results of the analysis show that service quality has a positive and significant effect on customer loyalty through customer satisfaction. These findings indicate that improving service quality not only increases customer satisfaction, but also contributes significantly to building customer loyalty. Based on the results of this study, the Memed Welding and Dico Workshop is advised to continue to improve the quality of service in order to maintain customer satisfaction and loyalty that has been formed.